Persistent left superior vena cava accompanying congenital heart disease in children: Experience of a tertiary care center. Issue 3 (3rd January 2017) - Ari, Mehmet Emre; Doğan, Vehbi; Özgür, Senem; Ceylan, Özben; Ertuğrul, İlker; Kayalı, Şeyma; Yoldaş, Tamer; Örün, Utku Arman; Kaya, Özkan; Karademir, Selmin
Abstract : Background: This study focuses on determining concomitant persistent left superior vena cava (SVC) in patients with congenital heart disease (CHD). Methods: Between 2005 and 2012, a total of 2.663 patients with CHD, 88 (3.3%) of whom were diagnosed with persistent left SVC, were evaluated retrospectively. The demographic characteristics of patients, clinical and radiographic findings, echocardiography, cardiac catheterization, and angiography results obtained from the patients' records were reviewed. Results: The median age of the patients was 9.5 months, and 46 of the 88 (52.3%) patients were female. The most common concomitant CHD were ventricular septal defect, double outlet right ventricle (DORV), and tetralogy of Fallot (TOF). When the patients were compared according to their CHD, persistent left SVC frequency was significantly higher in those with DORV ( P <.001), TOF ( P =.04), patent ductus arteriosus ( P =.01), and atrial septal defect ( P =.03). Eighty‐three of the 88 (94.3%) patients with persistent left SVC had right SVC, and 5 (5.7%) had absence of the right SVC. Twenty‐seven of the 83 (32.5%) patients with double SVC had connected normal innominate vein. In all cases, right aortic arch association was seen in 14 (15.9%) patients. Eighty‐four (95.4%) of the patients were diagnosed by echocardiography prior to catheter angiography. Persistent left SVC drained to the coronary sinus in all cases. Conclusion: Increased awareness about the association of certain CHD with persistent left SVC and a careful echocardiographic examination can facilitate the diagnosis of persistent left SVC. In addition, precise prior diagnosis of persistent left SVC can prevent complications during surgery.